2022
DOI: 10.1002/chem.202201066
|View full text |Cite
|
Sign up to set email alerts
|

Different Enzyme Conformations Induce Different Mechanistic Traits in HIV‐1 Protease

Abstract: The influence of the dynamical flexibility of enzymes on reaction mechanisms is a cornerstone in biological sciences. In this study, we aim to 1) study the convergence of the activation free energy by using the first step of the reaction catalysed by HIV-1 protease as a case study, and 2) provide further evidence for a mechanistic divergence in this enzyme, as two different reaction pathways were seen to contribute to this step. We used quantum mechanics/molecular mechanics molecular dynamics simula-tions, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This observation agrees with several studies of the dependence between the activation free energy and the reactant structure. It has been shown in several different systems, such as the HIV-1 protease, 39,40 α-amylase, 41,42 2′-hydroxyphenyl-2-sulfinate desulfinase, 43 or the human transmembrane protease serine 2 44 that the activation barrier depends critically on the fine pre-organization of the active site. In an enoyl-thioester reductase, it was experimentally shown that a mutation causing a displacement of 1 Å in the substrate caused a change of six orders of magnitude in forming an otherwise undetectable side-product.…”
Section: Resultsmentioning
confidence: 99%
“…This observation agrees with several studies of the dependence between the activation free energy and the reactant structure. It has been shown in several different systems, such as the HIV-1 protease, 39,40 α-amylase, 41,42 2′-hydroxyphenyl-2-sulfinate desulfinase, 43 or the human transmembrane protease serine 2 44 that the activation barrier depends critically on the fine pre-organization of the active site. In an enoyl-thioester reductase, it was experimentally shown that a mutation causing a displacement of 1 Å in the substrate caused a change of six orders of magnitude in forming an otherwise undetectable side-product.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of aspartic proteases, the existence of a pair of active-site Asp residues, one neutral and one negative, allows overcoming the burden of deprotonating the very basic water molecule. While one of the Asp residues deprotonates the hydrolytic water molecule, the second Asp residue protonates the very basic aliphatic oxyanion that is generated by the water attack on the substrate’s carbonyl so the burden of the deprotonation is compensated by the simultaneous very exothermic protonation of the growing oxyanion. , In some cases, the protonation and deprotonation can be carried out by a single Asp residue …”
Section: Resultsmentioning
confidence: 99%
“…The latter represents an average over all proteins in the crystal and thus is the most important and informative of all structures. Our experience is that the x-ray structure can provide results similar to ensemble averages because it is an ensemble average itself. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations